1961
DOI: 10.1002/cpt19612151
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacology of the tetracycline antibiotics

Abstract: Some of the relevant features of the clinical pharmacology of the tetracycline antibiotics are reviewed, and, in particular, the absorption, excretion, and disposition in the body of the four homologues that are currently available for clinical use are compared. The relatively minor differences in the chemical structure of these drugs are accompanied by significant differences in some of their physical properties and by some quantitative differences in their absorption, excretion, and distribution in the body,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1962
1962
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Six samples of each concentration were extracted separately and determined on the same day. As shown in Table 2, this method had a satisfactory precision in the range of serum concentrations obtained with the doses of tetracycline used in clinical practice (11). At tetracycline concentrations of 2 and 7 ,ug/ml, the variation coefficients were 3.45 and 1.50%, respectively.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Six samples of each concentration were extracted separately and determined on the same day. As shown in Table 2, this method had a satisfactory precision in the range of serum concentrations obtained with the doses of tetracycline used in clinical practice (11). At tetracycline concentrations of 2 and 7 ,ug/ml, the variation coefficients were 3.45 and 1.50%, respectively.…”
Section: Resultsmentioning
confidence: 81%
“…The precision of the method was determined for two concentrations of tetracycline in serum within the therapeutic range, i.e., 2 and 7 ,ug/ml (11). Six samples of each concentration were extracted separately and determined on the same day.…”
Section: Resultsmentioning
confidence: 99%
“…1,3 Third, the demethyl derivative (Declomycin) has one known disadvantage, photosensitization,6,T and one pos¬ sible one, an increased incidence of anaphylactoid reactions,5 which mitigate against its replacing tetra¬ cycline as the analogue of choice in the group.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot say which of the constituents is responsible for the interaction and there are several possible mechanisms. Aluminium ions can chelate tetracyclines (Waisbren & Hueckel, 1950) as can ferrous and magnesium ions (Kunin & Finland, 1961) but in vitro studies with phenytoin have shown that chelate formation does not occur with magnesium, ferrous and calcium ions, although it does with copper (Glazko & Chang, 1972). Aluminium hydroxide and magnesium trisilicate form gels in the gastrointestinal tract and adsorption on the surface of these could explain the reduced phenytoin absorption.…”
Section: Interaction Between Phenytoin and Antacidsmentioning
confidence: 99%